4x+60=x+70-3x

Simple and best practice solution for 4x+60=x+70-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+60=x+70-3x equation:



4x+60=x+70-3x
We move all terms to the left:
4x+60-(x+70-3x)=0
We add all the numbers together, and all the variables
4x-(-2x+70)+60=0
We get rid of parentheses
4x+2x-70+60=0
We add all the numbers together, and all the variables
6x-10=0
We move all terms containing x to the left, all other terms to the right
6x=10
x=10/6
x=1+2/3

See similar equations:

| -5x-50=-10x+60 | | 4x+40=6x=10 | | -44+x=3x+40 | | -7x+45=2x+9 | | 4w-20=4w-20 | | 11x+47=-5x-49 | | 14x+3x+2=53 | | 9x+48=3x+96 | | 7x-27=-7x+15 | | x2+8x−84=0 | | 7x-27=7x+15 | | 5a-8=7a+12 | | -6|v|=0 | | 5^c=625 | | 4-(x+3)/2=-x-1 | | 5-8x+4x^2=0 | | 2x+2=5x-9 | | 9x+22=49 | | 3(x+1)=x+41 | | 3(2x-9)=4x-13 | | 7(x+5)=2(2x+25) | | p=(9)/(7)p+28 | | 4×2^2x-2-5×2^x-1+1=0 | | 12=1h-1h-1h-1h-1h-1h-1h-1h | | 15x+29(x-2)=249 | | {4×+5y=1 | | P(n,4)=32760 | | 5(x+3)+2(x-4)=2 | | 3=1.09^n | | v^2-242=0 | | 22=16+3×b | | 2/3x^2+1/6x+3=0 |

Equations solver categories